To Sandwich Technetium: Highly Functionalized Bis‐Arene Complexes [99mTc(η6‐arene)2]+ Directly from Water and [99mTcO4]−. Issue 3 (12th December 2019) - Nadeem, Qaisar; Meola, Giuseppe; Braband, Henrik; Bolliger, Robin; Blacque, Olivier; Hernández‐Valdés, Daniel; Alberto, Roger
Abstract: The labeling of (bio)molecules with metallic radionuclides such as 99m Tc demands conjugated, multidentate chelators. However, this is not always necessary since phenyl rings can directly serve as integrated, organometallic ligands. Bis‐arene sandwich complexes are generally prepared by the Fischer–Hafner reaction. In extension of this, we show that [ 99m Tc(η 6 ‐C6 R6 )2 ] + ‐type complexes are directly accessible from water and [ 99m TcO4 ] −, even using arenes incompatible with Fischer–Hafner conditions. To unambiguously confirm the nature of these unprecedented 99m Tc complexes, their rhenium homologous have been prepared by substituting naphthalene ligands in [Re(η 6 ‐C10 H8 )2 ] + with the corresponding phenyl groups. The ease with which highly stable [ 99m Tc(η 6 ‐C6 R6 )2 ] + complexes are formed under standard labeling conditions enables a multitude of new potential imaging agents based on commercial pharmaceuticals or lead structures. Abstract : Radioactively marked : Phenyl groups in functionalized organic molecules or pharmaceuticals are directly labeled with 99m Tc by the formation of highly stable sandwich complexes. The reaction is directly performed in saline solution with [ 99m TcO4 ] − under convenient conditions. It represents a general labeling strategy which is different from the standard bifunctional chelator approach.